SUSTAINABLE INNOVATIONS IN RUBBER PLANTATION MANAGEMENT - Keawnoi, Yongyut; Pakittawichit, Thananchakorn; Sukapramet, Supawat (Journal of Social Science and Cultural, 2024)
This research aims to 1) identify the challenges and obstacles faced by rubber plantations, 2) explore sustainable management practices for rubber plantations in economic, social, and environmental dimensions, and 3) propose innovative models for sustainable rubber plantation management across these dimensions. This qualitative study involved 22 key informants, selected purposively, who are experts in sustainable rubber plantation management. The informants include 6 government officials, 8 large-scale rubber plantation owners (with more than 19 rai per district), and 8 small-scale rubber plantation owners (with less than 19 rai per district). Data were collected through in-depth interviews using structured interview guidelines to assess performance, analyze issues, and develop innovative sustainable management practices. The findings reveal that rubber plantations face several significant challenges, including 1) price volatility, 2) insufficient government policies regarding rubber prices, and 3) low market prices. Additionally, most plantation owners have not yet adopted modern technologies such as drip irrigation systems and IoT technology, which are crucial for increasing productivity, reducing costs, and achieving sustainability in rubber plantations.